1995
DOI: 10.1172/jci117720
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of HIV-1. Correlation with maternal viral load and plasma levels of CD4 binding site anti-gp120 antibodies.

Abstract: Almost all childhood HIV-1 is now acquired through vertical transmission. Identifying factors that affect the rate of transmission may lead to the initiation of specific preventive strategies. In this study, antibody levels against different neutralizing epitopes on the envelope glycoprotein of HIV-1 (gpl20) were measured in HIV-1-infected pregnant women that either transmitted HIV-1 to their infants (18 women) or did not (29 women). Differences in levels of antibodies directed against the monomeric gpl20 mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 34 publications
1
23
1
Order By: Relevance
“…15 Viral transmission depends on maternal viral load 16 and the level of maternal antiviral antibodies. 17 No threshold value of virus load have been identified to distinguish between transmitting and nontransmitting mothers. 18 However, high maternal viral load is insufficient to completely explain vertical transmission of HIV-1.…”
Section: Placental Overview: Pathophysiology and Immunologymentioning
confidence: 99%
“…15 Viral transmission depends on maternal viral load 16 and the level of maternal antiviral antibodies. 17 No threshold value of virus load have been identified to distinguish between transmitting and nontransmitting mothers. 18 However, high maternal viral load is insufficient to completely explain vertical transmission of HIV-1.…”
Section: Placental Overview: Pathophysiology and Immunologymentioning
confidence: 99%
“…This hypothesis has been confirmed by results presented by Okamoto et al (1997). However, there appears to be no major discussion on the finding that broadly neutralizing antibodies present in high titers will be associated to non-transmission of HIV-1 (Sienna Workshop 1992, Scarlatti et al 1993b, Khouri et al 1995, Hutto et al 1996, Jansson et al 1997, Cologognesi et al 1997, Bongertz et al 1999, Louisirotchanakul et al 1999. Nevertheless, some studies do not detect any protection by neutralizing antibodies in VT (Parekh et al 1991, Kliks et al 1994, Hengel et al 1998, Mabondzo et al 1998.…”
Section: Humoral Immune Responsementioning
confidence: 81%
“…Antibodies specific for peptides in the envelope glycoprotein gp41 have also been reported to be associated to protection against VT (Ugen et al 1997). However, other studies have found no association with antibody specificity or titer and mother-to-child HIV-1 transmission (Parekh et al 1991, Robertson et al 1992, Halsey et al 1992, Khouri et al 1995, Louisirirotchanakul et al 1999. Nevertheless, it must be remembered that HIV-1 specific humoral immune response during pregnancy is known to be reduced (Mikyas et al 1997, Bongertz et al 1998.…”
Section: Humoral Immune Responsementioning
confidence: 99%
“…This is known to be the case for some plant viruses (Power 1992); more generally, the vertical transmission rate of many organisms depends on sufficient replication within the host, which is in turn implicated in harming the host (Kaye et al 1994;Moriya et al 1992;Khouri et al 1995;Mueller 1991;Biswas et al 1989;Timian 1974). A second random number, r2, also uniformly distributed between zero and one, represents the fraction of virulence attributable to fecundity loss, according to the formula 1 - (b, + ei)/b x = rl rz-Finally, a third random number, r3, determines the fraction of the offspring of infected hosts which are themselves infected.…”
Section: Evolution Of Vertical and Horizontal Transmission And Virulmentioning
confidence: 96%
“…A number of plant and animal viruses (reviewed in Power 1992;Mims 1981) spread by a combination of vertical and horizontal transmission. Among the medically important viruses of humans with both transmission modes are HTLV-I (Mueller 1991); HIV (Khouri et al 1995); human papilloma virus (Kaye et al 1994); and hepatitis Band C viruses (Biswas et al 1989;Moriya et al 1992). Mixed vertical and horizontal transmission also occurs for bacterial infections and has' been extensively documented in microsporidian parasites of arthropods (Mangin et al 1995;Zchori-Fein et al 1992;Ewald and Schubert 1989 and references therein).…”
mentioning
confidence: 99%